Bibliometric and visualization analysis of macrophages associated with osteoarthritis from 1991 to 2021 - Yang, Zhen; Lin, Jianjing; Li, Hui; He, Zihao; Wang, Kai; Lei, Liandi; Li, Hao; Xing, Dan; Lin, Jianhao (Frontiers in Immunology, 2022)
Background: Macrophages significantly contributes to symptomology and structural progression of osteoarthritis (OA) and raise increasing attention in the relative research field. Recent studies have shown that tremendous progress has been made in the research of macrophages associated with osteoarthritis. However, a comprehensive bibliometric analysis is lacking in this research field. This study aimed to introduce the research status as well as hotspots and explore the field of macrophages research in OA from a bibliometric perspective. Methods: This study collected 1481 records of macrophages associated with osteoarthritis from 1991 to 2021 in the web of science core collection (WoSCC) database. CiteSpace, VOSviewer, and R package “bibliometrix” software were used to analyze regions, institutions, journals, authors, and keywords to predict the latest trends in macrophages associated with osteoarthritis research. Results: The number of publications related to macrophages associated with osteoarthritis is increasing annually. China and the USA, contributing more than 44% of publications, were the main drivers for research in this field. League of European Research Universities was the most active institution and contributed the most publications. Arthritis and Rheumatism is the most popular journal in this field with the largest publications, while Osteoarthritis and Cartilage is the most co-cited journal. Koch AE was the most prolific writer, while Bondeson J was the most commonly co-cited author. “Rheumatology”, “Orthopedics”, and “Immunology” were the most widely well-represented research areas of OA associated macrophages. “Rheumatoid arthritis research”, “clinical symptoms”, “regeneration research”, “mechanism research”, “pathological features”, and “surgery research” are the primary keywords clusters in this field. Conclusion: This is the first bibliometric study comprehensively mapped out the knowledge structure and development trends in the research field of macrophages associated with osteoarthritis in recent 30 years. The results comprehensively summarize and identify the research frontiers which will provide a reference for scholars studying macrophages associated with osteoarthritis.